Epidemiological and Outcome Analysis of Orthopedic Implants Removal in Kathmandu University Hospital - Shrestha, R; Shrestha, D; Dhoju, D; Parajuli, N; Bhandari, B; Kayastha, SR (Kathmandu University Medical Journal, 2015)
Background Orthopedic Implant removal is one of the commonly performed elective orthopedic surgeries. Implants are generally removed after the purpose of keeping implant is solved by healing of the fracture, but there is no consensus whether routine implant removal should be a policy for all fractures that were fixed. Objective This study aims to analyze the epidemiology and outcome of implant removal surgery carried out in the past three years in Kathmandu University Hospital. Methods Patients who underwent implant removal between 2010 January to 2012 December constituted the study cohort. Demographic data, indications, types of hardware and location of fractures were recorded. Similarly, duration of surgery, type of anesthesia and duration of hospital stay were recorded. All the patients who had undergone implant removal in this three years period were called for follow up examination but those who were not able to come were interviewed on telephone. Results There were 275 implant removals constituting 7.8% of total orthopedic operations and 26.3% of fracture fixations. Male to Female ratio was 189: 86. Pediatric age group (34.5%) had the highest incidence of implant removal. Moderate sized implants were the commonest hardwares removed (63.2%). Femur (27.3%) followed by radius (26.9%) were the commonest bone for implant removal. Average operative time was 47.3 minutes with average hospital inpatient stay of 2.6 days. Commonest indication for the implant removal procedure was pain (45%). Conclusion Implant removal procedures are one of the most commonly performed elective orthopedic surgeries. Though, after orthopedic implants removal, pain relief can be expected but it is not so predictive and hence patient should be well counseled before and the indications for implant removal has to be evaluated for better patient satisfaction and safety. DOI: http://dx.doi.org/10.3126/kumj.v11i2.12489 Kathmandu University Medical Journal Vol.11(2) 2013: 139-143